Mechanisms of Amomum villosum essential oil in enhancing tilapia (Oreochromis niloticus) intestinal health - Xiangbing Zeng; Xiaoting Zheng; Chenghui Li; Junchao Ming; Hongbiao Dong; Jiasong Zhang (Aquaculture Reports)
Amomum villosum is a member of the ginger family to treat gastrointestinal diseases in humans. Supplementing the diet of tilapia (Oreochromis niloticus) with essential oil (EOA) can enhance digestive and intestinal antioxidant capacity. We conducted a comparative experiment using tilapia to further understand the potential molecular response mechanism to dietary EOA. Fish were divided into four groups with different feeding doses of EOA: L (2 g/Kg) group, M (4 g/Kg) group, and H (8 g/Kg) group, along with a control group without EOA supplementation. The level of inflammatory factors (TNF-α, IL-1) declined significantly in the EOA group. Comparative transcriptome of the intestines revealed differentially expressed genes (DEGs) in each group, which further revealed that enriched terms were closely related to important pathways such as PI3K-Akt signaling, cell adhesion molecules, regulation of actin cytoskeleton, and autoimmune thyroid disease. These pathways play significant roles in regulating various cellular processes and immune responses of intestines. Intestine metabolomic analysis indicated that dietary EOA caused changes in metabolic processes, particularly in nucleotide metabolism, indicating the potential impact of EOA on these processes. To identify key factors regulating the molecular response to EOA supplementation, a weighted gene co-expression network analysis combined with transcriptome and differential metabolites to identify key genes and metabolites. Glycitein and genistein are substances related to the metabolism of soybean meal were identified. Hmgb2, Parp11, Bcoll is considered to be the key genes, and has the immune regulation function. This study provides new insights into the molecular basis underlying the protective effects of dietary EOA in tilapia. The results can benefit the aquaculture industry by developing dietary strategies to improve the health and welfare of tilapia in intensive farming.